Elucidating the analogues of 3-bromopyruvate (3-BP) as inhibitors against human hexokinase II for the development of anti-dengue drugs - Tanbin, Suriyea; Mohd Razali, Nur Izzati; Ahmad Fuad, Fazia Adyani (Anataolia Science Academy, 2019)
Dengue is one of the most severe febrile diseases caused by Dengue virus (DENV), a single-stranded RNA virus of Flaviviridae family. Recently, it has been declared that glycolysis exhibited perturbation during DENV infection, which is explicitly governed by human hexokinase II (HKII). Our aim is to identify HKII inhibitors based on 3-bromopyruvate (3-BP), a known HKII inhibitor, as a query molecule through virtual screening and verified by inhibition assays. Virtual screening method comprised of ligand and structure-based analyses, while inhibition studies were conducted by using personal glucose meter (PGM) and enzymatic assay. Firstly, the analogues of 3-BP were screened through ligand-based screening using Ultrafast Shape Recognition CREDO Atom Types (USRCAT) program and compounds were selected based on similarity scores. Subsequently, all selected compounds were docked through structure-based screening using AutoDock4 software and selected based on the best binding energy, to be tested using enzymatic assay. Compound 8 (ZINC78456436) and compound 10 (ZINC39416010) have been selected based on the similarity scores (0.838 and 0.836) respectively, and the best binding energy, -4.05 kcal/mol and -4.80 kcal/mol, whereas 3-BP itself was shown to be -3.66 kcal/mol. At 1 mM concentration, both compounds 8 and 10 showed inhibitory effects on HKII with PGM reading signal of 29.9 mM and 31.9 mM, respectively. Meanwhile, the IC50 values for both compound 8 and 10 were determined to be 1.6 mM and 7.4 mM. In a nut shell, selected compounds have fruitfully shown inhibitory effects on HKII, which paved the way towards the discovery of new dengue therapeutics.